Identifying and Ranking the Factors Affecting Visionary Educational Leadership: A Mixed-Methods Approach (Case Study: Primary Schools in Tehran Metropolitan Area) - Khorasani, Fatemeh; Shafizadeh, Hamid; Ahmadi, Fakhredin; Afzal Khani, Maryam (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The aim of this study is to identify and rank the factors affecting visionary leadership in primary schools. Methodology: This research is applied in terms of its objective, descriptive-survey in terms of data collection, and classified as a mixed-method study with both qualitative and quantitative approaches within the inductive-deductive paradigm. The research method is fuzzy Delphi. The statistical population for the qualitative part consisted of professors in educational management, human resource management, and educational sciences. According to the research purpose, purposive sampling was conducted with a sample size of 18 participants. The statistical population for the quantitative part comprised school principals in the Tehran metropolitan area, with a non-probabilistic convenience sampling method used to determine a sample size of 58 principals. The data collection tools for the qualitative part were interviews, and for the quantitative part, a questionnaire. Validity and reliability were confirmed using the CVR index, Cohen’s kappa test, and test-retest methods. In the qualitative section, the qualitative data obtained from interviews were analyzed using Maxqda 2020 software and coding techniques. The quantitative analysis and final analysis were performed using the fuzzy Delphi method. Findings: Through the qualitative data obtained from exploratory interviews, 14 factors affecting visionary leadership were identified. These factors were then ranked using quantitative research methods. Conclusion: The results of the research indicate that strategic vision, communication with key stakeholders, self-esteem, and a holographic perspective are the most important factors influencing visionary leadership.